Reciprocal activation between STAT3 and miR-181b regulates the proliferation of esophageal cancer stem-like cells via the CYLD pathway. Issue 1 (December 2016) - Xu, Dan-dan; Zhou, Peng-jun; Wang, Ying; Zhang, Li; Fu, Wu-yu; Ruan, Bi-bo; Xu, Hai-peng; Hu, Chao-zhi; Tian, Lu; Qin, Jin-hong; Wang, Sheng; Wang, Xiao; et al.
Abstract Background Recent studies have suggested that cancer cells contain subpopulations that can initiate tumor growth, self-renew, and maintain tumor cell growth. However, for esophageal cancer cells, the relationship between STAT3, microRNAs and cancer stem cells remains unclear. Methods Serum-free culture was used to enrich esophageal cancer stem-like cells (ECSLC). Flow cytometry determined the proportion of ECSLC. qPCR were performed to examine expression level of stemness factors, mesenchymal markers, ATP-binding cassette (ABC) transporters, STAT3, miR-181b, CYLD. Western blot were performed to analyze the expression of STAT3, p-STAT3 and CYLD (cylindromatosis). BALB/c mice xenograft studies were conducted to evaluate the tumorigenicity of enriched ECSLC. Sphere formation assay and colony formation assays were employed to analyze the relationship between STAT3 and miR-181b. Luciferase assays were used to evaluate activity which CYLD is a target of miR-181b. Results Sphere formation cells (SFCs) with properties of ECSLC were enriched. Enriched SFCs in serum-free suspension culture exhibited cancer stem-like cell properties and increased single-positive CD44 + CD24-, stemness factor, mesenchymal marker expression ABC transporters and tumorigenicity in vivo compared with the parental cells. Additionally, we found that reciprocal activation between STAT3 and miR-181b regulated SFCs proliferation. Moreover, STAT3 directly activated miR-181b transcription in SFCs and miR-181b then potentiated p-STAT3 activity. Luciferase assays indicated that CYLD was a direct and functional target of miR-181b. Conclusion The mutual regulation between STAT3 and miR-181b in SFCs was required for proliferation and apoptosis resistance. STAT3 and miR-181b control each other's expression in a positive feedback loop that regulates SFCs via CYLD pathway. These findings maybe is helpful for targeting ECSLC and providing approach for esophageal cancer treatments.